Private matters : an educational campaign on preventive habits for urinary tract infection (UTI) - Foo, Zhan Hao (2019)
This paper presents Private Matters, Singapore’s first educational campaign on preventive habits for Urinary Tract Infection (UTI). Targeted at female undergraduates aged 19-23, Private Matters aimed to communicate and inform the target audience about the various causes of UTI, address their misconceptions and encourage the adoption of lifestyle measures to reduce the risk of UTI. The campaign was initiated by four final year students from the Wee Kim Wee School of Communication and Information. UTI has always been a prevalent issue in Singapore. Approximately 50% of women contract UTI at least once in their life and 20% of Singaporean women from ages 20-65 suffer at least one attack each year. The recurrent nature of the infection, as well as potential complications such as kidney failure if left untreated, poses a serious risk. Guided by strong insights from our formative research, the team sought to increase knowledge and behaviour levels of UTI through a digital-focused approach. Creative tactics include developing an original interactive game as well as showcasing the severity of the infection through various video concepts, such as a ‘livestream eating show’. Overall, Private Matters was successful as a campaign in communicating the causes and consequences of UTI and encouraging preventive behaviour, with a 11.3% increase in adoption of recommended behaviour. Other impact and output objectives set out were mostly achieved as well. Since the launch, Private Matters has achieved over 120,000 engagements, 17 media mentions, and numerous positive feedback received from campaign partners and our target audience.